Biobanking for Viral Hepatitis Research - Ho, Erwin; Van Hees, Stijn; Goethals, Sofie; Smits, Elke; Huizing, Manon; Francque, Sven; De Winter, Benedicte; Michielsen, Peter; Vanwolleghem, Thomas (Frontiers in Medicine, 2019)
Introduction Viral hepatitis is a worldwide, important health issue. The optimal management of viral hepatitis infections faces numerous challenges. In this paper, we describe how biobanking of biological samples derived from viral hepatitis patients collected both in-hospital and during community outreach screenings provides a unique collection of samples. Materials and Methods All samples and materials were provided with a study code within the SLIMS system Study protocols and an informed consent form were approved by the Antwerp University Hospital/University of Antwerp Ethical Committee. Systematic biobanking was initiated in October 2014. Collected sample types include: 1) serum and plasma of all newly diagnosed HBV, HCV, HDV and HEV positive patients; 2) left-over serum and plasma samples from all PCR analyses for HBV, HCV and HEV performed in the context of routine clinical care; 3) left-over liver tissue not needed for routine histological diagnosis after liver biopsy; and 4) additional virus-specific, appropriate sample types using a scientific rationale-based approach. A community outreach screening program was performed in three major Belgian cities. Serum, EDTA, Tempus Blood RNA and BD Vacutainer CPT were collected. CPT tubes were centrifuged on-site and mononuclear cells collected within 24 hours. Results Concerning community screening: 298 individuals supplied all 4 sample types. Samples were stored at -150°C and were logged in the biobank SLIMS database. Samples were used for HBV-related immunological and biomarker studies. DNA isolated from plasma samples derived from chronic HBV patients was used to investigate Single Nucleotide Polymorphism rs 1790008. Serum samples collected from chronic hepatitis C patients were used to assess the efficacy of HCV treatment. Peripheral Blood Mononuclear Cells (PBMC) isolated from chronic HBV patients and healthy controls were used for different immunological study purposes. Virus isolated from biobanked stool of a chronic hepatitis E patient was used to establish a mouse model for Hepatitis E infections, allowing further HEV virology studies. Conclusion The establishment of a biobank with samples collected both in-hospital and during community-outreach screening resulted in a unique, continuously expanding collection of biological samples which provides an excellent platform for prompt answers to clinically and translational relevant research questions.